PENGUASAAN AFIKSASI PADA MAKALAH MAHASISWA MALAYSIA UIN SUNAN AMPEL SURABAYA - Ira Eko Retnosari (EDU-KATA, 2019)
This article aims to describe the mastery of affixation on student papers Malaysia UIN Sunan Ampel Surabaya. The approach used in this article is descriptive qualitative. The data collection method is used documentation. Data collection procedures in this article are (1) the collection of papers, (2) copying papers, (3) readings papers, (4) marking with highlighter, (5) classification, (6) coding, (7) the manufacture of the card. Analysis of the data in this study used a qualitative descriptive method. In this method, use the following steps: (1) the selection of data, (2) classification of data, and (3) an explanation. In this article, the data in words in a Malaysian student papers UIN Sunan Ampel Surabaya. Meanwhile, the source of the data acquired from Malaysian student papers UIN Sunan Ampel Surabaya. This article analyzes the results found affixation process and the meaning of affixation include (a) prefix: pe(N)- ,ber-, se-, me(N)-, ter-, and di-. (b) suffix: an, -kan, –nya, and –i, (c) konfiks: me(N)-kan, ke-an, me(N)-i, ber- kan, di-kan, di-i, pe(N)-an, di-kan, di-nya, and se-nya.